Teacher's Generosity as the Counteraction to the Young People's Hardening Pedagogic - O. B. Akimova; A. S. Frants (Russian State Vocational Pedagogical University, 2015)
The paper analyzes the growing tendency for young people's harden- ing. According to the authors that phenomenon is caused by such current trends as the language degradation, the militaristic and alienation vocabulary predominance re- sulting in disdainful attitude towards the surrounding people. As a pedagogic counter- action to such trends, the authors consider the revival of the forgotten domestic moral values in educational sphere. Their objective is to contemplate the necessity of enrich- ing the educational institutions by means of the national moral and cultural potential.The research methodology basis is defined as the axiology principle substantiat- ing the humanistic importance of the specifics of teachers' vocabulary. To demonstrate the advantages of the humanistic vocabulary educational potential the authors com- pare the specifics of such notions as generosity and tolerance. They prove that the teacher's tolerant attitude to students deforms both the pedagogic theory and educa- tional practice. In contrast, the generous attitude favors the student's, as well as teacher's moral development. The process of the youth refinement can be facilitated by the large-scale revival of half-forgotten national humanistic values and the vocabulary reflecting such values.